Reflections on Islamic Education: the Authenticity of the Cosmological Phase of the Physical Creation of Prophet Adam and Eve - Hakim, Nur; Saefullah, Muhammad; Suyud El Syam, Robingun (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
Abstract The story of Adam and Eve's creation, as told in the narrative of the Prophet, offers many valuable lessons; however, this aspect has not been widely explored. This research aims to reveal the educational insights of Islamic teachings regarding the authenticity of the cosmological phases of the physical creation of Adam and Eve, as described in the story of the Prophet. The article is based on findings from a library research approach and was analyzed qualitatively. The results of the study conclude that the lesson from the physical creation of Prophet Adam is that he was appointed as the caliph on earth, a leader and ruler for humankind. This creation reflects the uniqueness and nobility of human beings, serving as a model for all future generations. Furthermore, Adam’s creation from clay contains lessons about human origins and the diversity of human physical forms worldwide. Meanwhile, the lesson from the creation of Eve from Adam’s rib emphasizes the formation of a strong bond of affection between them, creating a pair that complements one another and lives together in tranquility. This suggests that men and women were created as a unified entity, mutually dependent and supportive of one another. Overall, this study makes a significant contribution to Islamic education, particularly in its understanding of the cosmological aspects of the creation of Adam and Eve. Keywords: Islamic education, cosmological, physical creation, Prophet Adam and Eve.AbstrakKisah penciptaan Nabi Adam dan Hawa menawarkan banyak pelajaran berharga; namun, aspek ini belum banyak dieksplorasi. Penelitian ini bertujuan untuk mengungkap wawasan pendidikan dari ajaran Islam mengenai otentisitas fase-fase kosmologis penciptaan fisik Nabi Adam dan Hawa. Artikel ini didasarkan pada temuan dari pendekatan penelitian pustaka dan dianalisis secara kualitatif. Hasil penelitian menyimpulkan bahwa pelajaran dari penciptaan fisik Nabi Adam adalah bahwa ia diangkat sebagai khalifah di bumi, seorang pemimpin dan penguasa bagi umat manusia. Penciptaan ini mencerminkan keunikan dan kemuliaan manusia, yang menjadi teladan bagi semua generasi mendatang. Selain itu, penciptaan Adam dari tanah mengandung pelajaran tentang asal-usul manusia dan keragaman bentuk fisik manusia di seluruh dunia. Sementara itu, pelajaran dari penciptaan Hawa dari tulang rusuk Adam menekankan pembentukan ikatan kasih sayang yang kuat di antara keduanya, menciptakan pasangan yang saling melengkapi dan hidup bersama dalam ketenangan. Hal ini menunjukkan bahwa laki-laki dan perempuan diciptakan sebagai satu kesatuan yang saling bergantung dan mendukung satu sama lain. Secara keseluruhan, penelitian ini memberikan kontribusi pada pendidikan Islam, khususnya dalam memahami aspek kosmologis penciptaan Adam dan Hawa. Kata kunci: pendidikan Islam, kosmologis, penciptaan fisik, Nabi Adam dan Hawa.